THE INFLUENCE OF THE SPECIFIC CHARACTERISTICS OF MENTAL AND PHYSICAL DEVELOPMENT OF WEAK PRESCHOOL CHILDREN ON THE EDUCATIONAL PROCESS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Students who need help do not fall into one category according to their clinical description. There are several reasons why these students do not fall into the same category. These include the variety of reasons for the defect, as well as the different periods of time when the defect occurred. Among the students of the auxiliary school, together with students with persistent brain diseases (seizures, schizophrenia, etc.), students with brain damage in kindergarten and junior school age receive education